EFFECT OF LIGHT ON SKELETAL δ13C AND δ18O, AND INTERACTION WITH PHOTOSYNTHESIS, RESPIRATION AND CALCIFICATION IN TWO ZOOXANTHELLATE SCLERACTINIAN CORALS - Reynaud-Vaganay S.; Juillet-Leclerc A.; Jaubert J.; Gattuso J.P. (My University, 2001)
The respective role of environmental and physiological controls on the isotopic composition of coral skeletons is a matter of debate. It has been shown that δ13C can be affected by light, seawater δ13CDIC, nutrition, respiration, spawning, pH and temperature. We investigated the effect of light on photosynthesis, respiration, calcification, and stable isotope composition (δ13C and δ18O) of the skeleton in the zooxanthellate scleractinian corals Acropora sp. and Stylophora pistillata. Colonies were grown on glass slides under controlled conditions in the laboratory at low and high light (LL and HL: 132 and 258 μmol photons m-2 s-1). The average net photosynthesis of Acropora sp. was significantly higher under HL than under LL. The difference was not statistically significant for S. pistillata. The respiration rate did not change significantly in both species under the two light conditions. The calcification rate of S. pistillata under HL was 17-fold higher than under LL and 2.5-fold higher for Acropora sp. The average skeletal δ13C and δ18O of Acropora sp. were significantly more negative under LL than under HL. For S. pistillata, skeletal δ18O was significantly more negative in the LL than in the HL condition. The δ13C value of the skeleton deposited under LL was also more negative than under HL, although the difference was not statistically significant. The skeletal δ13C was significantly correlated with the rate of calcification, both in LL and HL. No correlation was found between skeletal δ13C and the following other physiological parameters: net and gross photosynthesis (Pn and Pg), respiration (R), and the Pg/R ratio. The increase of skeletal δ13C with increasing light seems to support the model of Goreau (1977). Zooxanthellae mostly fix 12C under HL, leading to an increased concentration of 13C in the common carbon pool which supplies dissolved inorganic carbon (DIC) for calcification. Hence, the skeleton deposited is isotopically enriched in 13C. This general model needs revision to accommodate the recent finding that calcification and photosynthesis draw carbon from two reservoirs (seawater and metabolic DIC), and that respiratory CO2 is the major source of DIC for calcification. It is suggested that zooxanthellae mostly fix 12C[DIC] in LL; the organic matter respired, the CO2 released, and the CaCO3 deposited being therefore isotopically light. Under HL condition, zooxanthellar photosynthesis uses both [12C]- and [13C]DIC. The photosynthetic products catabolized by the coral, as well the respiratory CO2 and the CaCO3 precipitated are therefore heavier.
Keywords: CORALS; ISOTOPES; OXYGEN; CARBON; CULTURE; LIGHT